Highly efficient homology‐directed repair using CRISPR/Cpf1‐geminiviral replicon in tomato - Vu, Tien Van; Sivankalyani, Velu; Kim, Eun‐Jung; Doan, Duong Thi Hai; Tran, Mil Thi; Kim, Jihae; Sung, Yeon Woo; Park, Minwoo; Kang, Yang Jae; Kim, Jae‐Yean (Plant biotechnology journal, 2020)
Summary Genome editing via the homology‐directed repair (HDR) pathway in somatic plant cells is very inefficient compared with error‐prone repair by nonhomologous end joining (NHEJ). Here, we increased HDR‐based genome editing efficiency approximately threefold compared with a Cas9‐based single‐replicon system via the use of de novo multi‐replicon systems equipped with CRISPR/LbCpf1 in tomato and obtained replicon‐free but stable HDR alleles. The efficiency of CRISPR/LbCpf1‐based HDR was significantly modulated by physical culture conditions such as temperature and light. Ten days of incubation at 31 °C under a light/dark cycle after Agrobacterium‐mediated transformation resulted in the best performance among the tested conditions. Furthermore, we developed our single‐replicon system into a multi‐replicon system that effectively increased HDR efficiency. Although this approach is still challenging, we showed the feasibility of HDR‐based genome editing of a salt‐tolerant SlHKT1;2 allele without genomic integration of antibiotic markers or any phenotypic selection. Self‐pollinated offspring plants carrying the HKT1;2 HDR allele showed stable inheritance and germination tolerance in the presence of 100 mm NaCl. Our work may pave the way for transgene‐free editing of alleles of interest in asexually and sexually reproducing plants.